PENGARUH PEMBIAYAAN PENDIDIKAN TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI GUNUNGJAYA SATU ATAP KABUPATEN PEMALANG - Ulum, Muh Bahrul; Harmono, Hasmono; Sutrisno, Sutrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine and analyze the effect of educational financing on student learning outcomes at Gunungjaya Satu Atap Public Junior High School, Pemalang Regency. This study used a quantitative approach with a survey method. The sample consisted of students at Gunungjaya Satu Atap Public Junior High School. Data were collected through questionnaires distributed to students and analysis of school financial documents. The results indicate a positive and significant relationship between educational financing and student learning outcomes. Adequate financing, including the provision of facilities and infrastructure and operational cost support, contributes positively to improving student learning outcomes. Furthermore, this study identified that efficient school financial management and parental participation in educational financing also influence student learning outcomes. The study concludes that educational financing plays a crucial role in improving the quality of education and student learning outcomes at Gunungjaya Satu Atap Public Junior High School. Recommendations for this study include increasing the allocation of the educational budget, improving the efficiency of school financial management, and increasing parental participation in supporting educational financing.